My status as an assassin obviously exceeds the hero's. 4 - Akai, Matsuri (Seven Seas, 2023)
"Sharpen your sword for revenge. Akira got summoned to another world along with his entire class, but it quickly became clear that the king who brought them there had ulterior motives. Framed for the murder of his own friend and ally, Akira has taken his newfound skills as an assassin on the run, gaining strength in secret to someday claim revenge. After meeting an elf-maiden names Amelia, he accompanied her back to her homeland, where he put an old elven grudge to rest. Now his journey takes him to the land of beast-men, searching for a smith worthy of the ultimate blade."--Back cover.